Encapsulation of Metronidazole in Biocompatible Macrocycles and Structural Characterization of Its Nano Spray-Dried Nanostructured Composite - Mirella Mirankó; Mónika Megyesi; Zsombor Miskolczy; Judit Tóth; Tivadar Feczkó; László Biczók (Molecules, 2021)
Due to the great potential of biocompatible cucurbit[7]uril (CB7) and 4-sulfonatocalix[4]arene (SCX4) macrocycles in drug delivery, the confinement of the pharmaceutically important metronidazole as an ionizable model drug has been systematically studied in these cavitands. Absorption and fluorescence spectroscopic measurements gave 1.9 × 105 M−1 and 1.0 × 104 M−1 as the association constants of the protonated metronidazole inclusion in CB7 and SCX4, whereas the unprotonated guests had values more than one order of magnitude lower, respectively. The preferential binding of the protonated metronidazole resulted in 1.91 pH unit pKa diminution upon encapsulation in CB7, but the complexation with SCX4 led to a pKa decrease of only 0.82 pH unit. The produced protonated metronidazole–SCX4 complex induced nanoparticle formation with protonated chitosan by supramolecular crosslinking of the polysaccharide chains. The properties of the aqueous nanoparticle solutions and the micron-sized solid composite produced therefrom by nano spray drying were unraveled. The results of the present work may find application in the rational design of tailor-made self-assembled drug carrier systems.